2014
DOI: 10.1371/journal.pone.0108236
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Role of Homology Arms in Gene-Targeting Vectors in Human Cells

Abstract: Random integration of targeting vectors into the genome is the primary obstacle in human somatic cell gene targeting. Non-homologous end-joining (NHEJ), a major pathway for repairing DNA double-strand breaks, is thought to be responsible for most random integration events; however, absence of DNA ligase IV (LIG4), the critical NHEJ ligase, does not significantly reduce random integration frequency of targeting vector in human cells, indicating robust integration events occurring via a LIG4-independent mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…Recently, we examined the relationship between the length of homology arms and targeting efficiency using a human pre-B lymphoma cell line, Nalm-6. 20) Our data showed that the frequency of targeted integration increased with increase in arm length, but so did the frequency of random integration. 20) Therefore, shorter arms may be preferable for suppressing random integration; however, in some cases, there is no other option but to design a vector with long arms.…”
Section: Effect Of Homology Arm Length On Gene-targeting Efficiency Tmentioning
confidence: 51%
See 3 more Smart Citations
“…Recently, we examined the relationship between the length of homology arms and targeting efficiency using a human pre-B lymphoma cell line, Nalm-6. 20) Our data showed that the frequency of targeted integration increased with increase in arm length, but so did the frequency of random integration. 20) Therefore, shorter arms may be preferable for suppressing random integration; however, in some cases, there is no other option but to design a vector with long arms.…”
Section: Effect Of Homology Arm Length On Gene-targeting Efficiency Tmentioning
confidence: 51%
“…20) Our data showed that the frequency of targeted integration increased with increase in arm length, but so did the frequency of random integration. 20) Therefore, shorter arms may be preferable for suppressing random integration; however, in some cases, there is no other option but to design a vector with long arms. The vector design strategy is discussed in detail in Section 4.…”
Section: Effect Of Homology Arm Length On Gene-targeting Efficiency Tmentioning
confidence: 51%
See 2 more Smart Citations
“…In several fungi, inactivation of the non-homologous end joining (NHEJ) pathway results in ∼100% gene targeting by virtue of undetectable levels of RI4, but unfortunately this is not the case in mammalian cells; for example, loss of DNA ligase IV (Lig4), which is indispensable for NHEJ5, can reduce RI of foreign DNA, but does not reduce RI of targeting vectors harbouring long homology arms678. Thus, the exact contribution of NHEJ to RI is still uncertain and undoubtedly an NHEJ-independent route for RI does exist.…”
mentioning
confidence: 99%